Unlearning: rethinking poetics, pandemics, and the politics of knowledge - Briggs, Charles L., author; Utah State University Press, publisher (Colorado State University. Libraries, 2021)
A provocative theoretical synthesis, Briggs questions intellectual foundations and charts new paths. Through a look back at his own works as well as critical readings, scholars can disrupt existing social and discourse theories across disciplines when they collaborate with theorists whose insights are not constrained by the bounds of scholarship.--Provided by publisher.
Disciplining folkloristics -- Contested mobilities: on the politics and ethnopoetics of circulation -- What we should have learned from Américo paredes: the politics of communicability and the making of folkloristics -- The coloniality of folklore: toward a multi-genealogical practice of folkloristics (with Sadhana Naithani) -- Rethinking psychoanalysis, poetics, and performance -- Dear Dr. Freud -- Toward a new folkloristics of health -- Moving beyond "the media": from trAdditionalization to mediatization -- Germ wordfare: the poetic production of medical panics -- From progressive extractivism to phyto-socialism: trees, bodies, and discrepant phytocommunicabilities in a mysterious epidemic.
Keywords: Folklorists; Folklore -- Study and teaching; Mass media and folklore; Applied folklore -- Study and teaching; Communication in folklore